The Association Between Genetic Variants, Pharmacokinetics, and Infliximab Efficacy in Pediatric Patients With Crohn's Disease in China - Wenhui Hu; Yan Feng; Ziqing Ye; Zifei Tang; Lai Qian; Yuhuan Wang; Ying Huang (Frontiers Media S.A., 2021)
Background: Infliximab is an effective therapy for Crohn's disease (CD). Early non-invasive predictors of disease remission allow for modification of treatments. The aim of this study was to investigate the associations between genetic variants, pharmacokinetics, and infliximab efficacy in pediatric patients with CD.Methods: This retrospective observational study included CD patients under infliximab therapy between August 2015 and December 2020. Information on demographics, laboratory tests, medication data, and disease activity index was collected. The trough levels of infliximab (TLI) and antibodies to infliximab (ATI) were measured at week 14, and reactive drug monitoring was performed during follow-up. Ten single-nucleotide polymorphisms involved in the NF-κB-mediated inflammatory response, pharmacokinetics, and therapeutic response to infliximab were genotyped.Results: A total of 62 pediatric CD patients were enrolled. The clinical remission (CR) rate was 69.4 and 63.2% at week 14 and week 30, respectively. TLI at week 14 was significantly independently associated with CR at week 14 and mucosal healing (MH) at week 30 (p = 0.007 and p = 0.025, respectively). The optimal TLI threshold level capable of distinguishing between the CR and non-CR groups was 2.62 μg/ml (p < 0.001, area under the curve = 0.79, sensitivity = 69.2%, specificity = 78.9%), while that capable of distinguishing between the MH and non-MH groups was 3.34 μg/ml (p < 0.001, area under the curve = 0.85, sensitivity = 78.6%, specificity = 79.4%). Rs3397 in TNFRSF1B was associated with time to ATI production in CD patients (p < 0.001).Conclusions: Higher TLI contributed to achieving MH. Genotyping rs3397 in TNFRSF1B may identify patients who are prone to generating immunogenicity to drugs.